The impact of immediate test score reporting on university students' achievement emotions in the context of computer-based multiple-choice exams. (December 2017) - Daniels, Lia M.; Gierl, Mark J.
Abstract: Test-taking is an emotion-laden event for many students. Typically, negative emotions are highest at the start of an examination and are replaced by positive emotions as the exam progresses. The impact of computer-based testing and immediate score reporting on students' emotions has not been examined. In Study 1, we evaluated university students' emotions at the end of a computer-based exam and found positive emotions more strongly endorsed than negative. In Study 2, we replicated this finding and used a quasi-experimental pre-post design to examine how emotions changed in response to real examination scores. Exam scores presented immediately had significant positive effects on relief, pride, and hope and negative effects on anxiety and shame even after controlling for the corresponding emotion at the end of the exam. The one exception was anger, which was not impacted by examination score. No interaction effects were found. Highlights: Positive emotions are more strongly endorsed than negative at the end of computer-based exams. Scores reported immediately further reduce feelings of anxiety and shame. Scores reported immediately further enhance relief, hope and pride. Immediate test score reporting had no effect on students' anger.